Acaulospora minuta, a new arbuscular mycorrhizal fungal species from subSaharan savannas of West Africa - Oehl, F.; Palenzuela, J.; Sánchez Castro, I.; Hountondji, F.C.C.; Tchabi, A.; Lawouin, L.; Barea, J-M.; Coyne, Danny L.; Silva, G.A. da (2011)
A new arbuscular mycorrhizal (AM) fungal species of the genus Acaulospora (Glomeromycota) was frequently recovered from both undisturbed and cultivated agro-ecosystems of sub-Saharan West Africa, namely in Benin. It abundantly reproduced spores in trap cultures using Sorghum bicolor, Dioscorea cayenensis and Dioscorea rotundata in the glasshouse, and pure, monosporic cultures were readily established on Hieracium pilosella and Sorghum bicolor. It forms bright yellow-orange to orange-brown spores, (150-)175-230 in diameter, that have minute pits that are 0.5-1.2(-1.8) μm in diameter, 0.5-1.1 μm deep, and 1.0-2.5 μm apart. The species superfi cially resembles Acaulospora scrobiculata, which forms subhyaline to olive creamy spores that have larger, more irregular and deeper pits. Acaulospora minutawas one of the most frequent AM fungi collected during a study in the Guinea and Sudan Savannas in Benin. It was frequently recovered from yam (Dioscoreaspp.) fields, cultivated during the first year following savanna clearance, but was not recovered from fi elds later in the crop rotation cycle from either traditional or intensive agricultural ecosystems. It was also not recovered from long-term (> 7 years) regenerating savanna, under fallow following cultivation, indicating the vulnerability of this fungus to mechanical and/or biological disturbance, even under traditional West African low-input agro-ecosystems.